Integrating in the Higgs portal to fermion dark matter - Freitas, Ayres; Westhoff, Susanne; Zupan, Jure (Arxiv, 2015)
Fermion dark matter (DM) interacting with the standard model through a Higgs portal requires non-renormalizable operators, signaling the presence of new mediator states at the electroweak scale. Collider signatures that involve the mediators are a powerful tool to experimentally probe the Higgs portal interactions, providing complementary information to strong constraints set by direct DM detection searches. Indirect detection experiments are less sensitive to this scenario. We investigate the collider reach for the mediators using three minimal renormalizable models as examples, and requiring the fermion DM to be a thermal relic. The Large Hadron Collider in its high-energy, high-luminosity phase can probe most scenarios if DM is lighter than about 200 GeV. Beyond this scale, future high-energy experiments such as an electron-positron collider or a 100-TeV proton-proton collider, combined with future direct detection experiments, are indispensable to conclusively test these models.